2014
DOI: 10.1590/s0103-84782014000400018
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact specular microscopy in aphakic and pseudophakic dogs

Abstract: Cataract is one of the most common ocular diseases in dogs, and phacoemulsifi cation is considered its treatment of choice. Posterior capsular opacity (PCO) is a frequent complication and may occur weeks or months after the surgery. It is known that intraocular lenses (IOL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
1
8
1
1
Order By: Relevance
“…The cell area was greater than that described by RODRIGUES et al (2006), and similar to that found by NAGATSUYU et al (2014). Hexagonality percent values were higher than those reported by NAGATSUYU et al (2014), but similar to those found by PIGATTO et al (2008). The differences between the means found in the present study and those found by ROBERTS et al (2006) are assumed to be due to the differences between the methods used and the breeds studied.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The cell area was greater than that described by RODRIGUES et al (2006), and similar to that found by NAGATSUYU et al (2014). Hexagonality percent values were higher than those reported by NAGATSUYU et al (2014), but similar to those found by PIGATTO et al (2008). The differences between the means found in the present study and those found by ROBERTS et al (2006) are assumed to be due to the differences between the methods used and the breeds studied.…”
Section: Resultssupporting
confidence: 76%
“…The mean endothelial cell density did not differ from that found by NAGATSUYU et al (2014) for dogs of different breeds. The cell area was greater than that described by RODRIGUES et al (2006), and similar to that found by NAGATSUYU et al (2014).…”
Section: Resultscontrasting
confidence: 57%
“…Due to the fact that there is no cellular retraction and it can be used in animals and living humans, specular microscopy is considered the gold standard technique for assessing the corneal endothelium in people and animals (MORITA, 1995;ABIB & BARRETO, 2001;PIGATTO et al, 2006;PIGATTO et al, 2008;FRANZEN et al, 2010;BERCHT et al, 2015;ALBUQUERQUE et al, 2015;COYO et al, 2016). Specular microscopy has also been employed in the evaluation of dogs undergoing cataract removal surgery (NAGATSUYU et al, 2014). Specular microscopy is a widely used tool in many researches, and been demonstrated to be extremely reliable, and reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial layer is of fundamental importance in maintaining the transparency of the cornea and changes in endothelial cells can occur due to aging, eye diseases, drugs or intraocular surgery. Specular microscopy is among the most reliable techniques for analysing the corneal endothelium (ABIB & BARRETO, 2001;NAGATSUYU et al, 2014). Normal endothelial parameters have already been established in some species using a specular microscope, including: humans, sheep, dogs, monkeys, horses, cats, and others (ABIB & BARRETO, 2001;ANDREW, S. et al 2001;PIGATTO et al, 2006;PIGATTO et al, 2008;FRANZEN et al, 2010;BERCHT et al, 2015;COYO et al, 2016;TERZARIOL et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation